Financing and Stimulation of Innovation Commercialization in Ukraine: Problems and Solutions - Matselyuh, N.P.; Demyanchuk, G.V. (Science and Innovation, 2024)
The article deals with the analysis of financial support of R&D commercialization in Ukraine, the crisis in the sphere of implementation of new technologies at the domestic enterprises, and with ways to stimulate the R&D commercialization.